IDENTIFIKASI MIKOSIS PARU PADA PASIEN TUBERKULOSIS DENGAN BTA POSITIF DI KOTA JAMBI - Ahmad Syarthibi; Rd Mustopa; Anggraini Anggraini (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2022)
Background: Smear positive TB patients take a long time to undergo treatment. Therapeutic antibiotics have the effect of attacking the causative organism and eliminating other bacteria that are not. This causes changes in the normal flora ecosystem so that natural microbial ecological disturbances occur. Imbalance of normal flora can result in colonization of respiratory tract fungi that will invade the mucosa and multiply. This study aimed to analyze the incidence of fungal infections in smear-positive TB patients which include the incidence of fungal infections, determine the types of fungi that infect and determine fungal infections based on the phase of ATD consumption in the observed patients. Method: A descriptive cross sectional design was used in this study. The patient came from several Microscopic Referral Health Centers in Jambi city. The TB examination was carried out at the puskesmas while the fungal examination was carried out at the Mycology Laboratory of the Health Polytechnic of the Ministry of Health, Jambi, TLM Department. Total sampling was carried out during the data collection period July - August 2021. Result: In the culture examination, it was found that 47.6% of the fungus in the sputum of the patients were observed. The percentage was found in male patients and pulmonary TB patients with treatment duration of more than 2 months/advanced phase. From the identification carried out, several types of fungi were found consisting of Candida Sp (60%), Aspergilus Sp (30%) and other fungi (10%) as the cause of mycoses. Conclusion : micosis were found on patients with Pulmonary TB and had 2 months duration of treatment and caused by Candida Sp. Infection.